Psychometric properties of the Arabic version of the Eco guilt and Eco grief scales - Emmanuelle Awad; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Katia Iskandar; Sami El Khatib; Sahar Obeid; Souheil Hallit; Feten Fekih-Romdhane (Scientific Reports)
Abstract The purpose of this study is to validate the Eco Guilt (EGuiQ-11) and Eco Grief (EGriQ-6) scales for the Lebanese population. Conducted in September 2023, this cross-sectional study utilized a snowball sampling method. A total of 763 adult participants provided consent and completed an online survey that included the following scales: the EGuiQ-11, the EGriQ-6, the Arabic Climate Change Anxiety Scale (CCAS), and the Depression Anxiety Stress Scales-8 (DASS-8). The Exploratory Factor Analysis (EFA) of the EGuiQ-11 revealed a good fit for a unidimensional model. Both the EFA and Confirmatory Factor Analysis (CFA) indicated excellent reliability, with a Cronbach’s alpha of 0.92 and a McDonald’s omega of 0.92. For the EGriQ-6, EFA and CFA results also supported a unidimensional structure with excellent reliability, reflected in an alpha coefficient of 0.83 and an omega coefficient of 0.84. No significant gender differences were observed in EGuiQ-11 (t(761) = 0.862, p = .389) and EGriQ-6 (t(761) = 0.401, p = .689) scores. Additionally, higher levels of Eco Guilt and Eco Grief were strongly linked to greater psychological distress and increased climate anxiety. These findings make it possible for researchers to use these scales, which assess environmental emotions, in future studies with Arabic-speaking populations in Lebanon. They also highlight the potential impact of environmental changes on mental health.